Influence of Manganes Doping into HA Powders on the properties of its Dense Bodies - A N, Natasha; Sopyan, Iis; Mel, Maizirwan; S., Ramesh (Malaysian Medical Association, 2008)
The effect of Manganese (Mn) addition on the Vickers hardness and relative density of nanocrystalline hydroxyapatite (HA) dense bodies were studied. The starting Mn doped HA powders was synthesizedv ia sol-gel method with Mn concentrationv ariesf rom 2 molo/ou p to 15 mol% Mn. The Mn doped HA disc samples were prepared by uniaxial pressing at 200MPa and subsequently sintered at 1300oC. Characterization was carried out where appropriate to determine the phases present, bulk density, Vickers hardness of the various content of Mn doped HA dense bodies. The addition of Mn was observed to inf luence the color appearanceo f the powdersa nd denseb odiesa s well. Higher Mn concentrationr esultedi n dark grey powders. lt was also found that the hardness and relative density of the material increaseda s the Mn content increaseda nd influencedb y the crystallinity of the prepared Mn doped HA powders.